Flow-induced vibration handbook for nuclear and process equipment - Pettigrew, M. J.; Taylor, Colette E.; Fisher, N. J. 1959- (John Wiley & Sons, Inc., 2022)
"Flow-induced vibration is the term for the phenomena of vibration and noise that is caused by fluid flow. Excessive flow-induced vibrations can cause fatigue or failure in process and plant equipment, which can in turn lead to operational disruptions, lost production, and costly repairs. Mechanical engineers can help avoid these issues by performing a flow-induced vibration analysis during the design phase of a project. Industries that employ plants with high capital costs, such as the nuclear, power, petrochemical, and aerospace industries, have a particular interest in understanding and mitigating flow-induced vibrations"-- Provided by publisher.
Keywords: Hydrodynamics.; Pressure vessels -- Fluid dynamics.; Pressure vessels -- Vibration.; Piping -- Fluid dynamics.; Chemical plants -- Piping -- Vibration.; Nuclear power plants -- Piping -- Vibration.; Pipe -- Fluid dynamics.; elektronické knihy; electronic books